Effects of Titanium Dioxide Nanoparticles against Salt and Heat Stress in Safflower Cultivars - Dinler, Burcu Seckin; Cetinkaya, Hatice; Koc, Fatma Nur; Gül, Volkan; Sefaoğlu, Fırat (FapUNIFESP (SciELO), 2024)
ABSTRACT This study aimed to determine the effects of titanium dioxide nanoparticle (TiO2NP) pretreatment on seeds of different safflower cultivars (Balci, Dinçer) under salt and heat stresses. The apparent effects on stress markers (malondialdehyde (MDA), hydrogen peroxide (H2O2) and superoxide radical (O2 •⁻) content), as well as changes in germination and physiological parameters (radicle and plumula weight and length measurements), were investigated. TiO2NP pretreatment caused an increase in radicle length and plumula fresh weight for the Balci cultivar under salinity. Furthermore, plumula dry weight was alleviated with TiO2NP pretreatment for both cultivars. TiO2NP pretreatment improved plumula dry and fresh weights for both cultivars under heat stress. In addition, MDA content decreased for both cultivars under heat stress but only for Balci under salt stress. The amount of O2 •⁻ radicals positively affected only the radicle for both cultivars under heat stress. This study is the first to document the alleviation of salt stress damage for the Balci safflower cultivar, and protection for both Balci and Dinçer cultivars under heat stress, using 200 ppm TiO2NP pretreatment.
Keywords: reactive oxygen species; nanoparticle; QK1-989; Carthamus tinctorious; Botany; 2. Zero hunger